2015
DOI: 10.1039/c4gc02453b
|View full text |Cite
|
Sign up to set email alerts
|

Towards the electrochemical conversion of carbon dioxide into methanol

Abstract: Electrocatalysis for carbon dioxide conversion into methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
298
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(319 citation statements)
references
References 210 publications
5
298
0
1
Order By: Relevance
“…[17,19,121] Additionally, proton reduction is ac ompetitive and kinetically competent pathway in water,t he preferred solvents ystem,s ot he design of catalysts that are selectivef or the CO 2 reduction reactioni s paramount. [20,120,123] …”
Section: Co 2 Rrmentioning
confidence: 99%
“…[17,19,121] Additionally, proton reduction is ac ompetitive and kinetically competent pathway in water,t he preferred solvents ystem,s ot he design of catalysts that are selectivef or the CO 2 reduction reactioni s paramount. [20,120,123] …”
Section: Co 2 Rrmentioning
confidence: 99%
“…However, and due to its thermodynamic stability and its relative kinetic inertness, a preliminary activation is required. At this regards, the use of electrochemical methods for the conversion and reduction of CO2 appears as an interesting strategy [7][8][9]. In addition, this technology coupled to a renewable energy source, such as wind or solar, could generate carbon neutral fuels or industrial chemicals that are conventionally derived from petroleum.…”
Section:  Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Among various photocatalysts developed, nanosized TiO 2 -basedm aterials are the most extensively used ones in photocatalytic systems because of their high stabilitya nd efficiency under ultraviolet (UV) irradiation. [3][4][5][6][7][8][9][10] In the three TiO 2 polymorphs that exist in nature, anatase and rutile or their mixed crystals have been extensively adopted in the fields of photocatalysis and dye-sensitized solar cells (DSSCs), [3][4][5]11] whereas brookite is rarely investigated due to its thermodynamic metastability. [12] Although it was reported that brookite TiO 2 exhibited photocatalytic activity as earlya si n 1985, [13] there are very few researches on itsp hotocatalytic application because it is difficult to obtain pure-phase and highquality brookite TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Up to now,v arioust echniques, such as catalyzed chemical, electrochemical, photochemical, andp hotoelectrochemical processes, have been applied to convert CO 2 into useful chemicals. [1][2][3][4][5][6] Among these, the photocatalytic reduction of CO 2 with H 2 Ot os olar fuels is considered to be the most promising and attractive approach since it can not only convert CO 2 into clean solarf uels but also store the solar energy in those chemical fuels. [3][4][5][6][7][8][9][10] Among various photocatalysts developed, nanosized TiO 2 -basedm aterials are the most extensively used ones in photocatalytic systems because of their high stabilitya nd efficiency under ultraviolet (UV) irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation